Big data management framework for effective drug inventory management system in the United Arab Emirates (UAE) - Ahmed Mohammed, Mohammed Farid (2025)
Effective drug inventory management (DIM) is critical for ensuring continuous medication availability, minimizing wastage, and improving patient care. In the United Arab Emirates, healthcare institutions face persistent challenges such as fragmented data systems, inefficient distribution, and weak decision-making processes. This study introduces a conceptual framework based on Big Data Management (BDM) principles to enhance DIM effectiveness, grounded in three key theories: Information Processing Theory (IPT), which emphasizes data-driven decision-making; Resource-Based View (RBV), which positions big data capabilities as strategic assets; and the Rational Decision-Making Model (RDMM), which structures the decision-making process. Five core BDM factors identified through the Big Data Analytics Capability (BDAC) framework—data integration, data processing, data quality, data security, and information sharing were examined for their influence on effective decision-making, modeled as a mediating variable. A quantitative research design involving 293 healthcare professionals was employed, and Structural Equation Modeling (SEM) was used to test seven hypotheses (H1–H7). The results support the proposition all five big data management (BDM) factors significantly impact decision-making (H1–H5), which in turn positively influences DIM outcomes (H6), with additional evidence suggesting a potential feedback loop (H7). This study contributes to both academic theory and practical healthcare management by validating a big data management (BDM) -based framework that supports data-driven policies, robust infrastructure, and cross-functional integration to optimize inventory performance in healthcare institutions. This research also contributes to the theory and practice by clarifying the role of big data in healthcare inventory management and offering a validated framework for policymakers and practitioners. It also highlights the need for robust data infrastructure, integrated systems, and a decision-oriented culture in healthcare settings to ensure more effective drug inventory operations.